Enhanced Production of Microbial Cellulases as an Industrial Enzyme - A Short Review - Sarwan, Jyoti; Vijaya; Uddin, Nazim; Bose K, Jagadeesh Chandra (Journal of Multidisciplinary Research Advancements, 2024)
Enzymes are biocatalysts that exist with the ability to degrade complex molecules. Enzymes play a major role in every individual's life and for commercial purposes. Various microbes can produce high-yield enzymes. Microbial cellulases have an integral part in our biosphere because cellulose is present in abundance on our earth. Cellulose is a major component of every plant cell, and it is responsible in plant cells to maintain processes like photosynthesis. The methodology for this review paper involved an extensive literature review to gather information on the production and industrial applications of microbial cellulases. Relevant data was collected from scientific journals, research papers, and reputable online databases and was thoroughly analyzed to identify key concepts and emerging trends. The primary motive of this study was to compile all the numerous applications of cellulases as well as to describe some strategies to modify microbial cellulases with the help of genetic engineering and other tools in brief. This study has involved describing the structure, role, and mode of action, economic importance, and strain improvement of cellulases. Cellulases have applications in various sectors such as pharma, food, brewery, paper, pulp, textile, detergent, and many more. This study mainly focuses on microbial cellulases retarding chemical cellulases with their versatile behavior.